Adoption and impact of water-saving technologies in the Nagarjuna Sagar Project area of Andhra Pradesh - M Balasubramanian; P Anbukkani; M L Nithyashree; K Krishna Reddy; T Arivelarasan (Agricultural Economics Research Review, 2023)
Under the Climate Change and Adaptation (ClimaAdapt) programme, in the Nagarjuna Sagar Project area of Andhra Pradesh, water-saving interventions were conducted. To examine their impact, a study was carried out in the districts Nalgonda (Telangana) and Guntur (Andhra Pradesh). In all three water-saving interventions—alternating wetting and drying, modified System of Rice Intensification, and direct sowing of rice—capacity-building raised crop yield and farmer income. The direct seeded rice method reduced the cost of cultivation by about INR 11,000 per hectare.